THE USER-CREATOR OF NEW MEDIA AND CINEMATOGRAPHICAL THINKING - GUDAUSKAS, ANDRIUS (Knygotyra, 2014)
In our contemporary world, when new technologies are becoming more and more intensive, the habits of media users are inevitably changing. The practical behaviour of media users is altering in such a way that passive receivers of information are now becoming active mediate users. Due to this dramatic transformation, the situation of new media has become interminable. It means that evident changes have not yet acquired their final determination or any stable theoretical background or explanation. However, we must not forget the elementary scientific and practical truth that every new expression of the media in all ages (from spoken word, books, newspapers, magazines to the internet) is formed on the basis of practical expressions as well as on valuable theoretical discourse. The prospect of the evolution of practical media and of communicational sciences shows that media of the past influences the recent media. This universal axiom of science and culture can be considered an evident factor which is a starting point for any discourse on our social or cultural experience as well as on the socio-cultural future prospects. The article discusses the problem of the possibility for the user-creator of new media – the internet, to make an effective use of postmodern cinema practice and theory (by Gilles Deleuze) in order to understand the trajectory of both practical and transcendent thinking. Deleuze states that the postmodern European cinema has become a conceptual instrument, which stimulates the spectator to create his own meanings, because they are not provided directly. At the cinema, long plan-sequences, which have not yet undergone any montage cuttings, provide every help for constructing one’s own narration based on the cinematographical material. The spectator has to search for a hidden meaning and in a way he has to make a psychological analysis of himself. This kind of research stimulates the prolific imagination and creativity of the spectator. This new situation enables the user of the media to become an active and responsible creator of proper life, when innumerable choices are opening before his eyes. Therefore, if we have in mind these consistent patterns and analogically consider new media user’s situation, it is possible to agree with Manovich, that the everyday users of the internet are able and have to create a meaningful narrative for themselves, if only they care for the problem of meaning. A new media user does it in a similar way as a creator of classical cinema; which means that as a user of new media he gets his single plans from a data base and then he constructs his structure of sintagma-story-narrative. Deleuze’s theory was dealing with the problem of space montage inside the cinema camera object-glass long before the internet appeared. On the whole, the theories of the modern cinema can be helpful for a better understanding of newest internet media and for its influence on the conscious and subconscious mind of modern man. In other words, the ideological weight of classical cinema is getting smaller, while the weight of creative power stimulated by the internet in creative personalities is becoming greater.
Keywords: ...